Tribo-dynamics of differential hypoid gears - Mahdi Mohammadpour; Stephanos Theodossiades; Homer Rahnejat (2013)
Differential hypoid gears play an important role on the Noise, Vibration and Harshness (NVH) signature of vehicles. Additionally, friction developed between their teeth flanks under extreme loading conditions adds another source of power loss in the drivetrain which can mitigate vibrational energy. The paper considers the coupling between dynamics and analytical tribology to study dynamic response of hypoid gear pairs with lateral motion of support shafts also included in the analysis framework. Friction of teeth flank pairs is assumed to follow elastohydrodynamic lubrication under elliptical point contact geometry with lubricant film behavior conforming to Non-Newtonian thermal shear, also with surface asperity interactions. Tooth Contact Analysis (TCA) has been used to obtain the input data required for the investigation. The dynamic behavior and efficiency of a differential hypoid gear pair under realistic operating conditions is determined. The proposed tribo-dynamic framework provides a useful platform to conduct an extensive series of parametric studies.